The life of Buddhism - Reynolds, Frank, 1930-; Carbine, Jason A., 1971- (Berkeley : University of California Press, 2000)
Bringing together fifteen essays by outstanding Buddhist scholars from Asia, Europe, and North America, this book offers a distinctive portrayal of the "life of Buddhism." The contributors focus on a number of religious practices across the Buddhist world, from Sri Lanka to New York, Japan to Tibet.
Preliminaries; Contents; Note to the reader; General Introduction; 1. Temples and Monastic Complexes (Japan); 2. Image Consecrations (Thailand); 3. State Rituals and Ceremonies (Myanma); 4. Village Rituals and Ceremonies (Thailand); 5. The Ordination of Monks and Novices (Korea); 6. Female Renunciants (Myanma[r]/Burma); 7. Meditation (Japan); 8. The Monastic Quest; 9. Monastic Funerals (Thailand); 10. Lay Identity and Participation (China); 11. Cosmology and Law (Tibet); 12. Cosmology and Healing (Sri Lanka); 13. Devotional Rituals: Recent Innovations (Sri Lanka); 14. Death and Beyond (Japan).
Includes bibliographical references (pages 221-225) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Buddhism; Religious life -- Buddhism; Buddhism -- Customs and practices; Bouddhisme; Bouddhisme -- Coutumes et pratiques; Vie religieuse -- Bouddhisme; Buddhism; RELIGION -- Buddhism -- General; Buddhism; Buddhism -- Customs and practices; Religious life -- Buddhism; Humaniora -- Religionsvidenskab